Two Locomotor Traits Show Different Patterns of Developmental Plasticity Between Closely Related Clonal and Sexual Fish - Laskowski, Kate L.; Seebacher, Frank; Habedank, Marie; Meka, Johannes; Bierbach, David (Frontiers in Physiology, 2021)
The capacity to compensate for environmental change determines population persistence and biogeography. Within the lifetime of an individual, developmental plasticity mediated through epigenetic mechanisms can result in changes in gene expression and ultimately long-lasting modifications to its phenotype. However, epigenetic changes are not independent from genetics, because epigenetic modifiers themselves are encoded by DNA so that developmental plasticity may be contingent on genetic diversity. Here we tested whether a clonal fish (Poecilia formosa) with no genetic variation among individuals exhibits developmental plasticity in response to the early life thermal environment in two traits related to locomotion. We raised clonal offspring at 22oC and 28oC for 25 weeks, followed by short-term acclimation (three weeks) to a common temperature (25oC) before measuring critical sustained swimming performance (Ucrit) and unforced activity in an open field at 18, 22, 28, 34, and 38oC acute test temperatures. Differences in the developmental environment led to a shift in the thermal performance curve of unforced activity patterns, but much less so in maximal locomotor capacity. As a comparison, we also measured the same responses in the closely related and sexually reproducing Poecilia mexicana, which exhibited the opposite pattern: developmental plasticity was present in maximal locomotor capacity, but not in unforced activity. Our data show that genetically identical individuals can express different phenotypes in response to differences in their developmental environment. Importantly, however, the strength of epigenetic responses varies between traits. Comparisons with a sexually reproducing species indicate that genetic mechanisms may be important in mediating plastic responses.